Can the International Criminal Court Deter Atrocity? - Jo, Hyeran (2016)
Whether and how violence can be controlled to spare innocent lives is a central issue in international relations. The most ambitious effort to date has been the International Criminal Court (ICC), designed to enhance security and safety by preventing egregious human rights abuses and deterring international crimes. We offer the first systematic assessment of the ICC's deterrent effects for both state and nonstate actors. Although no institution can deter all actors, the ICC can deter some governments and those rebel groups that seek legitimacy. We find support for this conditional impact of the ICC cross-nationally. Our work has implications for the study of international relations and institutions, and supports the violence-reducing role of pursuing justice in international affairs